Strong impact of protonation and deprotonation on intermolecular Coulombic decay - Kryzhevoi, Nikolai V.; Cederbaum, Lorenz S. (Journal of physics. Conference Series, 2012)
Intermolecular Coulombic decay (ICD) is an ultrafast relaxation mechanism of a highly excited system embedded in a chemical environment. Our theoretical investigation of ammonia clusters shows that the ICD efficiency can be regulated by protonation or deprotonation. It is suggested that by varying ICD rate through changing the environmental pH value a control over the relaxation dynamics can be achieved.
Gesehen am 26.10.2018